KY. CONST. OF 1891, § 1(7) - (:unkn) unknown (General Publisher, 1891)
The right to bear arms in defense of themselves and of the State, subject to the power of the General Assembly to enact laws to prevent persons from carrying concealed weapons.
--
Keywords: GUARANTEED RIGHT